Functional electrical stimulation therapy for severe hemiplegia: Randomized control trial revisited: La simulation électrique fonctionnelle pour le traitement d'une hémiplégie sévère : un essai clinique aléatoire revisité. (April 2017) - Marquez-Chin, Cesar; Bagher, Shaghayegh; Zivanovic, Vera; Popovic, Milos R.
Background: Stroke is the leading cause of long-term disability. Stroke survivors seldom improve their upper-limb function when their deficit is severe, despite recently developed therapies. Purpose: This study aims to assess the efficacy of functional electrical stimulation therapy in improving voluntary reaching and grasping after severe hemiplegia. Method: A post hoc analysis of a previously completed randomized control trial (clinicaltrials.gov, No. NCT00221078) was carried out involving 21 participants with severe upper-limb hemiplegia (i.e., Fugl-Meyer Assessment–Upper Extremity [FMA-UE] ≤ 15) resulting from stroke. Findings: Functional Independence Measure Self-Care subscores increased 22.8 (±6.7) points in the intervention group and 9 (±6.5) in the control group, following 40 hr of equal-intensity therapy. FMA-UE score changes were 27.2 (±13.5) and 5.3 (±11.0) for the intervention and control groups, respectively. Implications: The results may represent the largest upper-limb function improvements in any stroke population to date, especially in those with severe upper-limb deficit.